2009
DOI: 10.2343/geochemj.1.0027
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitrogen deposition and its impact to Lake Sihwa in South Korea from January 2004 to September 2005

Abstract: Atmospheric wet and dry deposition samples collected from three sites (Hwasung, Ansan and Daeboo) around Lake Sihwa, South Korea were used to calculate the atmospheric deposition of nitrogen to the lake and to evaluate its effects on primary production. The analytical parameters included pH, conductivity, and cation (Na + , NH 4 + , K + , Mg 2+ , Ca 2+ ) and anion (Cl -, NO 3 -, SO 4 2-) concentrations. The monthly volume-weighted mean pH of the rainwater ranged from 3.9 to 5.1, with a mean of 4.5, thus showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Extensive use of fossil fuels and N in fertilizer has already impacted coastal as well as open ocean marine ecosystems due to increased N deposition (e.g. Paerl 1997;Spokes and Jickells 2005;Jung et al 2009;Zhang et al 2010;Krishnamurthy et al 2010). Duce et al (2008) have estimated that in 1860, atmospheric deposition flux of total reactive N (i.e.…”
mentioning
confidence: 99%
“…Extensive use of fossil fuels and N in fertilizer has already impacted coastal as well as open ocean marine ecosystems due to increased N deposition (e.g. Paerl 1997;Spokes and Jickells 2005;Jung et al 2009;Zhang et al 2010;Krishnamurthy et al 2010). Duce et al (2008) have estimated that in 1860, atmospheric deposition flux of total reactive N (i.e.…”
mentioning
confidence: 99%
“…Because the Shihwa Basin includes areas with industrial, agricultural, and coastal land use, the study are has experienced serious problems with air pollution [34][35][36][37].…”
Section: +mentioning
confidence: 99%
“…In comparison to other water surfaces (Table ), the magnitude of the total N deposition flux to NT2R is similar to the deposition on the coastal Barnegat Bay, New Jersey (Gao, ), but lower than on the Great Bay Estuary, New Jersey (Ayars & Gao, ). Jung et al () reported also a higher value of 16.6 kgN·ha −1 ·year −1 for the total annual deposition of N to Lake Shiwa under the influence of high anthropogenic emissions of NO x and NH 3 from urban sources or long‐range transport of N species. Over Lake Dianchi in China, Zhan et al () estimated the highest value of N dry deposition flux (11.17 kgN·ha −1 ·year −1 ) with a contribution of 94% for gaseous N species (10.5 ± 0.3 kgN·ha −1 ·year −1 ) and 6% for particulate inorganic N species (0.67 ± 0.1 kgN·ha −1 ·year −1 ).…”
Section: Resultsmentioning
confidence: 98%
“…Dry deposition fluxes over reservoirs or water bodies are scarce in the literature, particularly for gaseous species. Indeed, studies on nitrogen deposition to water surface (rivers, bays, and lakes) have rather focused on dry deposition of aerosol particles (Chen et al, ; Gao, ; Jung et al, ). For example, Ayars and Gao () estimated a total particulate N ( p NH 4 + + p NO 3 − ) dry deposition of 1.54 kgN·ha −1 ·year −1 over the Mullica River‐Great Bay Estuary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation